A Pharmacokinetic Study of Antimalarial 3, 5-Diaryl-2-aminopyridine Derivatives. (29th March 2015) - Dambuza, Ntokozo; Smith, Peter; Evans, Alicia; Taylor, Dale; Chibale, Kelly; Wiesner, Lubbe
Abstract : Malaria caused by Plasmodium falciparum is responsible for approximately 80% of the incidence and 90% of deaths which occur in the World Health Organization (WHO) African region, with children and pregnant women having the highest incidence. P. falciparum has developed resistance, and therefore new effective candidate antimalarial drugs need to be developed. Previous studies identified 3, 5-diaryl-2-aminopyridines as potential antimalarial drug candidates; therefore, derivatives of these compounds were synthesized in order to improve their desired properties and pharmacokinetic (PK) properties of the derivatives were investigated in a mouse model which was dosed orally and intravenously. Collected blood samples were analyzed using liquid chromatography coupled to mass spectrometer (LC-MS/MS). The mean peak plasma level of 1.9  μ M was obtained at 1 hour for compound 1 and 3.3  μ M at 0.5 hours for compound 2. A decline in concentration was observed with a half-life of 2.53 and 0.87 hours for compound 1 in mice dosed orally and intravenously, respectively. For compound 2 a half-life of 2.96 and 0.68 hours was recorded. The bioavailability was 69% and 59.7% for compound 1 and compound 2, respectively.